2007
DOI: 10.1016/j.jcrs.2007.05.030
|View full text |Cite
|
Sign up to set email alerts
|

Posterior chamber phakic intraocular lens (ICL) for hyperopia: Ten-year follow-up

Abstract: The results confirmed the long-term safety, efficacy, accuracy, and predictability of ICL implantation for hyperopia. The Collamer material was well tolerated in all eyes.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

6
71
1
4

Year Published

2009
2009
2024
2024

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 106 publications
(86 citation statements)
references
References 9 publications
(5 reference statements)
6
71
1
4
Order By: Relevance
“…67 Of the pIOLs available, 68 the Visian ICL (Staar Surgical, Monrovia, CA, USA) offers the longest safety track record for an injectable pIOL and is available in a wide range of powers (including toric correction up to 6D). Pesando et al 69 reported retrospective 10-year follow-up data in 59 ICLimplanted hypermetropic eyes, showing a mean endothelial cell loss of 4.7%, mostly occurring within the first few weeks of implantation and remaining almost unchanged thereafter. Edelhauser et al 70 reported prospective, multicenter, 4-year follow-up data on 526 eyes with a 2-3% cell loss rate over the first 3 years, followed by a cell increase of 0.1% between years 3 and 4, suggesting that endothelial remodelling and stability may have been achieved.…”
Section: Refractive Correction-piol Implantationmentioning
confidence: 99%
“…67 Of the pIOLs available, 68 the Visian ICL (Staar Surgical, Monrovia, CA, USA) offers the longest safety track record for an injectable pIOL and is available in a wide range of powers (including toric correction up to 6D). Pesando et al 69 reported retrospective 10-year follow-up data in 59 ICLimplanted hypermetropic eyes, showing a mean endothelial cell loss of 4.7%, mostly occurring within the first few weeks of implantation and remaining almost unchanged thereafter. Edelhauser et al 70 reported prospective, multicenter, 4-year follow-up data on 526 eyes with a 2-3% cell loss rate over the first 3 years, followed by a cell increase of 0.1% between years 3 and 4, suggesting that endothelial remodelling and stability may have been achieved.…”
Section: Refractive Correction-piol Implantationmentioning
confidence: 99%
“…49 Previous reports of posterior chamber phakic IOL surgery report an incidence of lens opacity from 1.5% to 25%. 23,50,51 Some of the variation may be due to the definition of cataract or opacity and the follow-up period, as well as surgical technique. In our series, lens opacity was noted in three eyes (11.11%).…”
Section: Discussionmentioning
confidence: 99%
“…16 Phakic intraocular implants can correct high myopia and hyperopia, with the advantages of reversibility, stability of the correction, and to a great extent, preservation of accommodation. 8,[17][18][19][20][21][22][23][24][25][26] An increasing number of procedures are being performed because of the expectation of a superior quality of vision obtained with phakic intraocular lens (IOL) implantation with respect to keratorefractive surgery for the correction of high ametropias. [27][28][29][30] However, induced cataract and glaucoma are at the heart of most concerns regarding these intraocular surgical procedures, especially for posterior chamber phakic IOLs.…”
mentioning
confidence: 99%
“…However, over the past quarter of a century, the introduction and refinement of excimer laser (7)(8)(9)(10)(11) , refractive lens exchange, multifocal (12) and phakic intraocular lens technologies (13) have heralded a new era in refractive surgery and offer promise for the correction of hyperopia. Published studies of hyperopic laser photorefractive keratectomy (H-PRK) and hyperopic laser in situ keratomileusis (H-LASIK) have demonstrated both efficacy and safety and such procedures are now in wide-spread clinical usage (7)(8)(9)(10)(11) .…”
Section: Introductionmentioning
confidence: 99%